5PSQ-110 Computerised physician order entry systems and related clinical decision support tools in inpatient care – barriers of cost-effectiveness. (March 2019) - Bella, R; Langer, A; Csanádi, M; Zemplényi, A; Botz, L
Abstract : Background: Medication errors (ME) and the consequent preventable adverse drug events (pADE) are a major burden on inpatient care. They are not only a possible source of patient harm but may lead to increased healthcare cost due to prolonged length of stay (LOS) as a consequence of pADEs. Computerised Physician Order Entry (CPOE) occasionally with a clinical decision support tool (CDS), has been shown to increase patient safety, and it is essential for patient-level medication ordering. Due to the scarce financial resources of clinics and inpatient care, exploration of new ways for being more cost-effective is essential. Purpose: Studies examining CPOE systems in inpatient care were collected with cost or other resource utilisation-related outcomes. Development of these services might be a good opportunity to expand clinical pharmacist competencies. Material and methods: We conducted a systematic search of Scopus, PubMed and Web of Science databases. Search terms were determined according to PICO. Non-English papers and studies providing no original data were excluded. Results: One-thousand six-hundred and ninety-three abstracts were screened, thereafter 67 full text articles were analysed, of which 27 met the inclusion criteria. We have identified 18 partial and nine full economic evaluations. Apart from one cost-benefit and one cost-utility analysis, all the publications included were cost-effectiveness studies. The clinical outcomes were dominated by pADE, although LOS (one case) and QALY (one case) were also apparent. In contrast, the input parameters were quite different. Every analysis demonstrated cost-reduction and patient safety enhancement but methodological differences were present in terms of perspective, discounting, duration, inflation, sensitivity, inputs and definitions (e.g. definition of ADE). Conclusion: The different outcome data types used in studies counter the intention to prove the cost-effectiveness of CPOE systems. It is clear that no generally accepted definition is present over which system can be called CPOE. On the other hand, it will only be possible to compare different CPOEs if common agreement is developed in terms of outcomes observed by studies. Clinical pharmacists can play an important role in the unification of the upcoming studies and collection of data. References and/or acknowledgements: Thanks to the help of my co-workers and the guidance of our leaders. No conflict of interest.